PEMBERDAYAAN MAHASISWA MELALUI INOVASI KEWIRAUSAHAAN BERBASIS PRODUK LOKAL DI UNIVERSITAS DHYANA PURA - Ni Putu Dyah Krismawintari; Ni Luh Putu Suarmi Sri Patni; IWK Tejasukmana (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2025)
The Community Service Program (PKM) themed “Student Empowerment through Local Product-Based Entrepreneurial Innovation” was carried out by Dhyana Pura University in the 2025 Fiscal Year as an effort to strengthen students’ capacity in initiating culinary businesses based on local ingredients. The activity involved five students and three supervising lecturers who provided guidance in the areas of marketing management, finance, and human resource management. The program was implemented through training, production practice, business model development, digital marketing, and the provision of production equipment assistance. The results show an improvement in students’ technical and managerial skills, as well as the creation of culinary products such as brownies cookies, cheese cake, coffee/non-coffee beverages, and banana nuggets. Further mentoring through the Dhyana Pura University Business Incubator serves as a sustainability strategy to develop independent and competitive young entrepreneurs.